Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s12160-008-9033-z
|View full text |Cite
|
Sign up to set email alerts
|

Small Changes in Nutrition and Physical Activity Promote Weight Loss and Maintenance: 3-Month Evidence from the ASPIRE Randomized Trial

Abstract: More modest behavioral changes are capable of promoting weight loss, decreasing adiposity markers and sustaining these changes over 3 months. Longer-term studies comparing this approach with traditional behavioral weight loss treatments are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 17 publications
4
67
0
Order By: Relevance
“…The threshold model [51] postulates, though, that the stimulus can be brief if it is at a proper threshold of intensity. Research with the Graded Exercise Protocol [55] showed that after a graded warm-up to a 4-min work segment at~75 % VO 2max with twice-aweek training produced about the same increase in CRF as much as longer duration training at the same intensity. Very similar outcomes including favorable changes in glucose metabolism and blood pressure (BP) with a single, harder 3-4 min workpiece have PRACTICE AND PUBLIC HEALTH POLICIES been found by a prominent Norwegian research group [56] and Gibala's group in Canada [52].…”
Section: Very Brief Aerobic Training To Improve Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The threshold model [51] postulates, though, that the stimulus can be brief if it is at a proper threshold of intensity. Research with the Graded Exercise Protocol [55] showed that after a graded warm-up to a 4-min work segment at~75 % VO 2max with twice-aweek training produced about the same increase in CRF as much as longer duration training at the same intensity. Very similar outcomes including favorable changes in glucose metabolism and blood pressure (BP) with a single, harder 3-4 min workpiece have PRACTICE AND PUBLIC HEALTH POLICIES been found by a prominent Norwegian research group [56] and Gibala's group in Canada [52].…”
Section: Very Brief Aerobic Training To Improve Treatmentmentioning
confidence: 99%
“…Recent exercise science studies have shown that higher intensity interval training protocols safely produce, even for people with prominent risk factors, improved health-related outcomes versus typical low to moderate intensity protocols with the same energy expenditure [49][50][51][52][53][54][55][56]. However, those interval protocols have multiple repeats, raising the question of translatability [49,50,[52][53][54].…”
Section: Very Brief Aerobic Training To Improve Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the 12% increase in consumption in this study is fairly modest, even small changes in behaviors like diet and exercise have been shown to have meaningful health benefits (72). We also note that the intervention itself was very modest-just one exposure to guidelines a month before the choice task.…”
Section: Case Study: Evolution Of Nutrition Guidelinesmentioning
confidence: 63%
“…The first objective was to develop the Aspiring to Lifelong Health (ASPIRE) Coaching Fidelity Checklist (ACFC) to measure and report fidelity in the delivery of a weight management intervention. ASPIRE is an evidence-based treatment weight management program using a small changes approach that has been shown to be effective in several previous studies across 3, 6, 9, and 12 months [16][17][18]. The measure for the present study was developed and tested based on the largest and most recent study completed to date with 12-month outcomes.…”
Section: Introductionmentioning
confidence: 99%